E-commerce and digitalization drive Indonesian export growth, competitiveness, and global market expansion - Ni Ketut Masih; I Gede Wahyu Antara Kurniawan; I Ketut Suarja (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This study examines how the expansion of e-commerce and the broader digital economy influences Indonesia’s export growth across provinces and sectors. Building on evidence that digitalization and e-commerce enhance export volumes and competitiveness but also generate regional disparities and supply‑chain frictions, the research aims to quantify these effects and identify strategic policy levers. Using panel data for 34 provinces from 2013–2023, the study constructs a composite digitalization index (internet infrastructure, e‑commerce intensity, digital payments) via the entropy method and estimates fixed‑effects and mediation models linking digitalization, sectoral composition, and exports. Econometric analysis tests heterogeneity between western/central and eastern regions and the mediating role of MSME digital adoption and logistics performance. The findings are expected to show that stronger digital development is associated with higher export volumes, especially for MSMEs, while weaker regions and sectors risk being left behind. The paper concludes with policy recommendations for digital infrastructure, skills, and export‑oriented e‑commerce ecosystems to support inclusive export growth.